2007
DOI: 10.1177/000313480707301019
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Obesity and Postoperative Complications in a Veterans Affairs Medical Center General Surgery Population

Abstract: Patients who are obese are believed to be at greater risk of developing intraoperative and postoperative complications than their nonobese counterparts. Many studies have shown that there is a higher prevalence of obesity among the Veterans Affairs patient population. We performed a retrospective review of 941 patients presenting to a single Veterans Affairs Medical Center. We aimed to determine the incidence of obesity among the Veterans Affairs Medical Center general surgery patient population as well to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the literature on the effect of obesity on outcomes following general and colorectal surgery is less clearcut. Interestingly, several studies on morbidity following general and colorectal procedures have failed to show any effect of obesity on outcomes21–25. Radical prostactectomy but not cystectomy has been shown to be more expensive in obese patients, although in these studies underweight patients were included in the ‘normal’ weight group and this may have affected any differences seen26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on the effect of obesity on outcomes following general and colorectal surgery is less clearcut. Interestingly, several studies on morbidity following general and colorectal procedures have failed to show any effect of obesity on outcomes21–25. Radical prostactectomy but not cystectomy has been shown to be more expensive in obese patients, although in these studies underweight patients were included in the ‘normal’ weight group and this may have affected any differences seen26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…The mean BMI in our cohort was low in comparison to many studies assessing postoperative outcome among patients with excess weight because these studies assessed obese patients as a single group [ 13 , 24 , 30 32 ]. It is frequently reported that obese patients undergoing surgery have a high prevalence of comorbidities such as diabetes, hypertension and sleep apnea which can adversely affect surgical outcome [ 24 ].…”
Section: Main Textmentioning
confidence: 85%
“…Obesity-related risks appear to have significantly reduced with the introduction of laparoscopy, especially for procedures popularly known as providers of postoperative complications in the obese [ 18 20 , 41 44 ]. Nonetheless, the association between obesity and adverse surgical outcome may not be clear-cut as contradictory reports are available [ 7 , 32 , 40 , 45 ]. It is often suspected that the numerous previous reports pointing obesity as a risk factor of adverse surgical outcome may have inspired the over-reporting of postoperative complications in obese patients [ 46 ].…”
Section: Main Textmentioning
confidence: 99%
“…A S THE PREVALENCE of obesity continues to increase in the United States, the surgical population has seen a proportional rise in obese patients. 1 Studies cite that body mass index (BMI) indicating obesity (BMI > 30) may pose as a risk factor for poor surgical outcomes. [2][3][4] Over the last two decades, physicians in many surgical fields have recommended weight reduction as a preoperative intervention, but thus far, little is known about the success rate, risk, or value of such endeavors.…”
mentioning
confidence: 99%